Data-driven security : analysis, visualization, and dashboards - Jacobs, Jay (Data analyst); Rudis, Bob (Indianapolis, IN : Wiley, 2014)
Security professionals need all the tools at their disposal to increase their visibility in order to prevent security breaches and attacks. This careful guide explores two of the most powerful data analysis and visualization. You'll soon understand how to harness and wield data, from collection and storage to management and analysis as well as visualization and presentation. Using a hands-on approach with real-world examples, this book shows you how to gather feedback, measure the effectiveness of your security methods, and make better decisions.
The Journey to Data-Driven Security -- Building Your Analytics Toolbox: A Primer on Using R and Python for Security Analysis -- Learning the "Hello World" of Security Data Analysis -- Performing Exploratory Security Data Analysis -- From Maps to Regression -- Visualizing Security Data -- Learning from Security Breaches -- Breaking Up with Your Relational Database -- Demystifying Machine Learning -- Designing Effective Security Dashboards -- Building Interactive Security Visualizations -- Moving Toward Data-Driven Security.
Includes bibliographical references and index : pages 314-331.
2024.
Keywords: Computer networks -- Security measures; Information visualization; Computer security